Synthesis and characterization of CuCrO2 delafossite nanoplatelets through Rietveld refinement and Pair distribution function analysis - Kjær, Emil Thyge Skaaning (UCPH NanoScience - a student research journal, 2018)
Delafossite (ABO2) nanostructures such as CuCrO2 nanoparticles have shown promising properties in dye-sensitized solar cells (DSSCs). Previous studies have shown that changing the metal on either the A or B site in the structure, influences both the conditions required to synthesize delafossite compounds, their properties, and their tendency of forming nanocrystals or bulk particles. The crystallites can further be doped changing the conductivity further. Here, we present a series of syntheses with varying parameters, illustrating how the conditions must be optimized to obtain the pure delafossite CuCrO2phase. Structure characterization was done through Powder X-ray Diffraction (PXRD) showing change in crystallite size with increasing synthesis time and temperature. By varying both temperature and time, the amount of secondary phase (CuO) in the final product can be minimized. It was only possible to synthesize pure delafossite when certain criteria regarding pH, temperature and time were met. Rietveld refinement of the PXRD data showed anisotropic nanocrystallites with approximate sizes of 130x130x40Å with the trigonal delafossite unit cell. However, the crystallites are too small and anisotropic to give a satisfying fit using conventional Rietveld refinement, and the sizes were obtained through anisotropic “no rules” model. Pair Distribution Function (PDF) analysis of X-ray total scattering data were used to obtain further understanding of structural disorder in the crystallites.